Sistem Pakar Diagnosa Gizi Buruk Pada Balita Berbasis Mobile Menggunakan Metode Certainty Factor - Afdal Muhammad Efendi; Tengku Khairil Ahsyar; M Afdal; Febi Nur Salisah; Syaifullah Syaifullah (Universitas Budi Darma, 2023)
Maltnutrition has a significant impact on children’s development and is a common problem in developing countries, including Indonesia. There are many factors that contribute to malnutrition, one of which is the lack of understanding and knowledge among parents regarding childcare and proper nutrition. This has motivated the author to develop an expert system application for diagnosing malnutrition in toddlers, aiming to facilitate the community, especially mothers with toddlers, in early diagnosis of malnutrition symptoms and diseases through mobile devices. This expert system application is built using Java Programming language with the assistance of Android studio as the development tool. The system analysis employed is the Unified Modeling Language (UML) to provide an overview of the application to be created. Testing is conducted using the Black Box method and data validation yields nearly 100% accuracy. The calculation for diagnosing symptoms and diseases utilizes the Certainty Factor methode, which serves as the calculation of value within the expert system application. The testing results based on symptoms and diseases through the applied calculation method achieve a 92% accuracy rate. The development of this application is expected to assist the community, especially mothers with toddlers, in identifying early symptoms and diseases of malnutrition in children, as well as obtaining solutions for the experienced illnesses.